Precise indoor localization anywhere and anytime - Mao, Kaiyi (2018)
This report summarizes what the author has done during the final year project period and presents the results and findings throughout last whole year. Firstly, the background and motivation for studying indoor positioning techniques is discussed. The author decided to focus on the OFDM simulation model for single antenna provided by institutional supervisor. Then the author studied the OFDM simulation model and improve the algorithm. The mathematical models and algorithms are discussed for both single antenna and antenna array. Also, the choices of parameters are discussed to increase the accuracy and efficiency. The mathematical method to calculate velocity of the target by using two antennas are discussed as well. Furthermore, the author implements the algorithms by using MATLAB to calculate the distance, relative speed and velocity of an object in indoor environment. Thereafter, the author did test and analyzed the results of simulation; then improve the algorithm to make sure a high accuracy every time. Two methods to take average for antenna array are compared also. Finally, the applications for indoor positioning system and future works in further development can be done are discussed.